A New Comparative View? (KULT_online, 2020)
When it comes to ‘comparison,’ which is something from everyday life and represents at the same time an efficient way to construct meanings and relationships, we all have certain ideas about its functioning and significance. Therefore, this anthology takes a closer look at comparison in relation to its form, function, and implementation at the interface between cultural studies and natural sciences. The collection of contributions represents a tangible result of a long-standing cooperation between the research group of ‘Comparative Zoology’ and the research division ‘The Technical Image’ at Humboldt University, Berlin. ‘Comparison’ or ‘comparative visual analysis’ is taken as the fundamental approach for scientific examinations in exploring interdisciplinary methodologies and formulating applicable procedures of comparison in cultural and artistic discussions as well as in natural sciences.